Establishment and evaluation of a UPLC-MS/MS method for simultaneous determination of bongkrekic acid and dehydroacetic acid in rice noodles - Zhao, Lingguo; Lv, Ronggui; Song, Jiang; Chen, Xi; Lei, Lei; Zeng, Weixian; She, Miaowen; Li, Dabing; Yu, Xiaxia; Liu, Zhanguo; Wang, Xiao; Liu, Yong (Frontiers in Chemistry, 2025)
A UPLC-MS/MS method with one-step extraction and simultaneous determination of bongkrekic acid (BA) and dehydroacetic acid (DHA) in rice noodles has been established in this study for the first time. The extraction solvent consisted of a mixture of methanol, ammonia, and water. Electrospray ionization negative ion mode (ESI-) was used for multiple reaction detection and external standard method was used for quantitative determination. The method demonstrated a good linearity range of 0–50 ng/mL with a correlation coefficient (r) of 0.9998 for BA, and showed a linearity range of 0∼500 ng/mL with r of 0.9993 for DHA. The limits of detection (LOD) were determined to be 0.1 μg/kg for BA and 0.6 μg/kg for DHA. Additionally, the method exhibited good recovery of 90.1%∼105.4% for BA and 80.4%∼102% for DHA. Meanwhile, the method also exhibited good precision with RSD of 0.4%∼7.5% for BA, and with RSD of 4.5%∼11.4% for DHA. Furthermore, the established method was sucessfully applied to the analysis of rice noodles from two production enterprises. BA was detected in one rice noodle sample and DHA was detected in 7 rice noodle samples in the enterprises A which was the manufacturer of food consumed by the poisoned patient. To investigate the cause of death of the poisoned patient, the toxigenic bacterium Burkholderia gladiolus was isolated and cultured to produce BA. The results showed that the established method could also be used to qualitatively screen BA and its isomer isobongkrekic acid (IBA) in GVC enrichment broth, potato glucose agar and rice sample, which facilitates a rapid and accurate judgement of whether the isolated bacterium strain produces BA. With high sensitivity and accuracy, and simple sample pretreatment, the proposed method shows potential for safety assessment of the entire production process of rice-derived products, addressing a significant public health concern.